Penyuluhan dan Pelatihan Pemanfaatan Talas dan Kulit Kopi menjadi Produk Bernilai Ekonomi di Desa Bone-Bone - Asrul Hidayat; Zaldi Harun; Mirna Ismayani; Fitra Wahyuni; Aulia Aulia; Syaparuddin Syaparuddin; Nur Aisa; Tiara Wulan Dari Derang; Hasra Hasra; Asty Asty; Muhammad Aslan Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This community service program was carried out in Bone-Bone Village, focusing on the utilization of local potential, namely taro and coffee husks, to be developed into economically valuable products such as taro donuts and coffee husk tea. The main problems faced by the community were the lack of knowledge about the diversification of local food products and limited skills in processing simple materials into marketable products. The implementation methods included counseling on the importance of food processing innovation, hands-on training in producing taro donuts and coffee husk tea, as well as mentoring in basic business management such as packaging and marketing strategies. The results of the program indicated an increase in the community’s understanding and skills in processing local resources into creative and competitive products. In addition, this activity provided motivation for the community to develop micro-enterprises based on village potential, which is expected to improve family income and support village self-reliance.